Bacillus aciditolerans sp. nov., isolated from paddy soil. Issue 4 (28th February 2019) - Ding, Meng-Jiao; Shang, Nian-Jie; Xiao, Zhi-xin; Shao, Fei; Liu, Li; Huang, Ying; Zhou, Lu-kuo; Zhou, Ji-Heng; Zhang, Yi
Abstract : A Gram-stain-positive, motile, rod-shaped bacterial strain, YN-1 T, was isolated from a rice field in the town of Jietou, Yunnan Province, PR China. Colonies were circular, 1–2 mm in diameter, creamy white, with slightly irregular margins. The isolate grew optimally at 37 °C, pH 7.0 and with 1.0 % (w/v) NaCl. On the basis of the results of 16S rRNA gene sequence similarity comparisons, YN-1 T clustered together with other species of the genus Bacillus and showed highest similarities with Bacillus onubensis 0911MAR22V3 T (98.0 %), Bacillus humi LMG22167 T (97.5 %), ' Bacillus timonensis ' 10403023 (97.4 %) and ' Bacillus sinesaloumensis' P3516 (97.1 %). However, the DNA–DNA hybridization values between YN-1 T and closely related strains of species of the genus Bacillus were well below 47 %, indicating that they represent different taxa. The average nucleotide identity and the Genome-to-Genome Distance Calculator also revealed low relatedness (below 95 and 70 %, respectively) between YN-1 T and type strains of closely related species of the genus Bacillus . The DNA G+C content of the strain was 40 mol%. The major cellular fatty acids were iso-C15 : 0, anteiso-C15 : 0, and C16 : 0 . The polar lipids were diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine, two unidentified phospholipids, three unidentified aminophospholipids and two other unidentified lipids. Physiological and biochemical test results were also different from those of the most closely related species. On the basis of the phenotypic, genetic and chemotaxonomic data, strain YN-1 T is considered to represent a novel species of the genus Bacillus, for which the name Bacillus aciditolerans sp. nov. is proposed, with strain YN-1 T (=CCTCC AB 2017280 T =JCM 32973 T ) as the type strain.